Morphological and Molecular Features of Porcine Mesenchymal Stem Cells Derived From Different Types of Synovial Membrane, and Genetic Background of Cell Donors - Siengdee, Puntita; Oster, Michael; Reyer, Henry; Viergutz, Torsten; Wimmers, Klaus; Ponsuksili, Siriluck (Frontiers in Cell and Developmental Biology, 2020)
Synovial mesenchymal stem cells (SMSCs) have become a great cell source for musculoskeletal stem cell research, especially related to cartilage and bone tissue regeneration, due to their superior cell proliferation properties and multidifferentiation potential into various cell lineages. This study revealed isolation methods, culture conditions, and morphological and molecular characterization of SMSCs derived fibrous synovium (FS) and adipose synovium (FP) of two pig breeds differing in growth performance (German Landrace (DL), and fat deposition (Angeln Saddleback (AS)). Herein, FS possessed nucleated cell numbers nearly twice as high as those of FP at Passage 0. SMSCs derived from different types of synovial membrane and genetic background show similar cell morphologies and immunophenotypes, which were assessed by cell surface epitopes and multilineage differentiation potential, but differ significantly in their molecular characteristics. In addition, transcripts of SMSCs from AS were more enriched in IGF-1 signaling and VEGF ligand receptor, while SMSCs from DL were more enriched in growth hormone signaling and bone metabolism. The results indicate that genetics and tissues play significant roles for SMSC characteristics so that SMSCs can be traced back to the original cell donor and be used for fine turning in applications of medical research and therapies.